Fluorescence "on–off–on" peptide-based chemosensor for the selective detection of Cu2+ and S2− and its application in living cell bioimaging. Issue 41 (21st September 2016) - Wang, Peng; Wu, Jiang; Su, Pingru; Xu, Cong; Ge, Yushu; Liu, Dan; Liu, Weisheng; Tang, Yu
Abstract : A novel fluorescence chemosensorL based on a tetra-peptide conjugated with dansyl groups has been designed as a promising analytical tool for detecting Cu 2+ and S 2− in 100% aqueous solutions and living cells. Abstract : Copper ions are known to be very important for homeostasis, which is critical for the metabolism and development of living organisms. In addition, sulfide ions, as an important endogenously produced gasotransmitter, have been proved to be implicated in a variety of physiological functions such as anti-apoptosis, vasodilation, antioxidation, and anti-inflammation. Herein, we report the development of a novel fluorescence chemosensor (L ) based on a tetra-peptide conjugated with dansyl groups as a promising analytical tool for detecting Cu 2+ and S 2− in 100% aqueous solutions, which exhibits excellent cell biotoxicity and intracellular biosensing ability. The chemosensorL displays an "on–off–on" response type fluorescence change upon the addition of Cu 2+ and S 2− to aqueous media and living cells. Moreover, L displays high selectivity and sensitivity with the detection limits for Cu 2+ and S 2− measured to be 88 nM and 75 nM, respectively. This study raises the new possibility of a highly selective and sensitive peptide-based fluorescence chemosensor for multifunctional detection, including cation and anions, using a successive fluorescence response strategy in environmental and biological systems.